ANALISIS KOMPARATIF TERHADAP PERUBAHAN STATUS HARTA WAKAF - Anggita Vela (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2015)
Waqf is the release of the property that is represented from the owner by withholding his principal treasures and giving charity for the sake of social interest for the common good. In changing the status of waqf property, the turn of the object and the purpose of the waqf are very strict in Syafi’i’s Imam, however, on the basis of an emergency and the principle of maslahat, among jurists like Imam Hanafi, the change can be made, So that the benefits of endowments that continue to continue as shadaqoh fingers, not mubadzir because it is damaged, does not work anymore and so forth. With that change, the status of the object as a waqf property is essentially undamaged. This research is basically aimed to know the view of Imam Syafi’i and Imam Hanafi regarding the change of wakaf’s property status, it can be understood that regarding the change of wakaf wealth status according to Imam Syafi’i it is said that the wakaf property that is not working anymore still can not be sold, Exchanged, replaced and transferred, except in a state of necessity the wakaf property can be exchanged or sold. Whereas Madzhab Hanafi is of the opinion that the waqf objects that have been or are not functioning anymore which is no longer in accordance with the allocation, it may sell, change, replace or move the wakaf objects, in order to function or bring maslahat in accordance with the purpose of waqf, or to obtain more maslahat Great for the public interest, especially the Muslims.